n-7-6=-9

Simple and best practice solution for n-7-6=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-7-6=-9 equation:


Simplifying
n + -7 + -6 = -9

Reorder the terms:
-7 + -6 + n = -9

Combine like terms: -7 + -6 = -13
-13 + n = -9

Solving
-13 + n = -9

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + n = -9 + 13

Combine like terms: -13 + 13 = 0
0 + n = -9 + 13
n = -9 + 13

Combine like terms: -9 + 13 = 4
n = 4

Simplifying
n = 4

See similar equations:

| (4z+7)/(z-19)=83/(z-19) | | -3-7a-7a=-17 | | 7x+8=13y+20 | | -5+x/-2=-2 | | 6m-6-2=22 | | (4z+7)/(z-19)=415/(5z-95) | | 7a-2+7a=12 | | 5a^2-2ab-16b^2= | | 31-x=43 | | -p+3p=-2 | | 42=5(x+8) | | -6x+1-6=1 | | 21y-49= | | .05x+.33-.75x+0.6666666667-0.8333333333x=8-1.4 | | 3.18-4=8.72 | | 2/3s=18 | | 11-10x=42x+19 | | 6x+11=-79-9 | | x+3/4=-1/2 | | x/(-1/6)=6/7 | | 4a-1=2a+27 | | 3x^2+2=59 | | X-15=3x | | x/-1/6=5/7 | | x/-1/6+6/7 | | 1.6s=-8 | | 6(4h-3)=3(5h-3) | | 0.1a-1.09=0.91 | | (1/2)(6x+7)=3x | | -11-6x=-9x | | 1/2z-3/5=12/5 | | 60m=60 |

Equations solver categories